Extracellular Nucleic Acids Present in the Candida albicans Biofilm Trigger the Release of Neutrophil Extracellular Traps - Smolarz, Magdalena; Zawrotniak, Marcin; Satala, Dorota; Rapala-Kozik, Maria (Frontiers in Cellular and Infection Microbiology, 2021)
Neutrophils, the first line of the host’s defense, use a variety of antimicrobial mechanisms to fight invading pathogens. One of the most crucial is the production of neutrophil extracellular traps (NETs) in the process called netosis. The unique structure of NETs effectively inhibits the spread of pathogens and ensures their exposure to a high concentration of NET-embedded antimicrobial compounds. Netosis strategy is often used by the host to defend against fungal infection caused by Candida albicans. In immunocompromised patients, this microorganism is responsible for developing systemic fungal infections (candidiasis). This is correlated with the use of a vast array of virulence factors, leading to the acquisition of specific resistance to host defense factors and available drug therapies. One of the most important features favoring the development of drug resistance is a C. albicans ability to form biofilms that protect fungal cells mainly through the production of an extracellular matrix (ECM). Among the main ECM-building macromolecules extracellular nucleic acids have been identified and their role is probably associated with the stabilization of the biofilm structure. The complex interactions of immune cells with the thick ECM layer, comprising the first line of contact between these cells and the biofilm structure, are still poorly understood. Therefore, the current studies aimed to assess the release of extracellular nucleic acids by C. albicans strains at different stages of biofilm formation, and to determine the role of these molecules in triggering the netosis. We showed for the first time that fungal nucleic acids, purified directly from mature C. albicans biofilm structure or obtained from the whole fungal cells, have the potential to induce NET release in vitro. In this study, we considered the involvement of TLR8 and TLR9 in netosis activation. We showed that DNA and RNA molecules initiated the production of reactive oxygen species (ROS) by activation of the NADPH oxidase complex, essential for ROS-dependent netosis. Furthermore, analysis of the cell migration showed that the nucleic acids located in the extracellular space surrounding the biofilm may be also effective chemotactic factors, driving the dynamic migration of human neutrophils to the site of ongoing fungal infection.